Knowledge on breast feeding and its techniques among health care workers in a tertiary health centre - Bhatia, Aril; K., Mithun H.; Sudhir, Shyam; Nuwera, Haleema (International Journal of Contemporary Pediatrics, 2020)
Background: Breast milk is optimum for a neonate as it is a natural food and the best gift a mother can give to her baby. Breast feeding is an art and skill which need to be learnt and mastered by mothers. As health care workers are the first line of contact for lactating mothers, this study was planned to assess their knowledge on breast feeding. Methods: Hospital based cross-sectional study was performed among health care workers at Yenepoya Medical College and Hospital of Mangalore. 100 health care workers consisting of 60 medical interns and 40 staff nurses were enrolled in the study. Health care workers were given a questionnaire that sought responses pertaining to the knowledge on breastfeeding and its techniques. The data were analyzed using Microsoft Access and Excel software. Results: The present study showed 92% of medical interns and 95% of nursing staff had correct knowledge about initiation of breastfeeding. Knowledge on contents of colostrums and its advantage was more among medical interns (85%) as compared to nursing staffs (30%). Knowledge on prelacteal feeds was good among medical interns as compared to nurses. Both medical interns and nursing have poor knowledge on breastfeeding during maternal illness. Knowledge on correct feeding position and good breast attachment was good among nursing staffs. Conclusions: Study showed there is some substantial knowledge gap on breastfeeding among health care workers. Enhancing their knowledge on breastfeeding and the problems associated with it will be useful for the nurturing mothers as well as themselves.